A Critical Analysis of the Empirical Ramification of Goods and Services Tax (GST) Implementation and Administration Through the National Information Utility (NIU) - Goods and Services Tax Network (GSTN) in the Republic of India - Kumar, Vikash (Digital Repository of Theses - SSBM Geneva, 2024)
This study explores the empirical ramifications of Goods and Services Tax (GST) implementation and administration through the Goods and Services Tax Network (GSTN) in India. Utilizing a qualitative approach, data was collected from interviews with 118 stakeholders, including business owners, tax professionals, government officials, and IT administrators. The study reveals that GSTN has facilitated significant improvements in the efficiency and transparency of GST processes. Key benefits include streamlined operations through automated tasks, enhanced compliance, and real-time data access, which have collectively contributed to a more efficient tax administration system. However, the study also identifies critical challenges that impede the full realization of GSTN’s potential. These challenges include frequent technical issues such as system downtimes and slow processing speeds, a complex and non-intuitive user interface, and inadequate support and training for users. These issues lead to increased compliance costs, cash flow disruptions, operational delays, market uncertainty, and reduced consumer confidence, impacting both businesses and the broader economy. The study further highlights the potential adverse effects of a GSTN failure on GST policy enforcement, including disruptions in tax filing and compliance, negative impacts on revenue collection, and increased administrative burdens. Despite these challenges, some respondents noted the adaptability of businesses and tax authorities through temporary workarounds, although these are not sustainable solutions in the long term.